Effects of 2‐year calorie restriction on circulating levels of IGF‐1, IGF‐binding proteins and cortisol in nonobese men and women: a randomized clinical trial. Issue 1 (6th October 2015) - Fontana, Luigi; Villareal, Dennis T.; Das, Sai K.; Smith, Steven R.; Meydani, Simin N.; Pittas, Anastassios G.; Klein, Samuel; Bhapkar, Manjushri; Rochon, James; Ravussin, Eric; Holloszy, John O.; ,
Summary: Young‐onset calorie restriction (CR) in rodents decreases serum IGF‐1 concentration and increases serum corticosterone levels, which have been hypothesized to play major roles in mediating its anticancer and anti‐aging effects. However, little is known on the effects of CR on the IGF‐1 system and cortisol in humans. To test the sustained effects of CR on these key hormonal adaptations, we performed a multicenter randomized trial of a 2‐year 25% CR intervention in 218 nonobese (body mass index between 22 and 27.8 kg m −2 ) young and middle‐aged (20–50 years age range) men and women. Average CR during the first 6 months was 19.5 ± 0.8% and 9.1 ± 0.7% over the next 18 months of the study. Weight loss averaged 7.6 ± 0.3 kg over the 2‐years period of which 71% was fat mass loss ( P  < 0.0001). Average CR during the CR caused a significant 21% increase in serum IGFBP‐1 and a 42% reduction in IGF‐1:IGFBP‐1 ratio at 2 years ( P  < 0.008), but did not change IGF‐1 and IGF‐1:IGFBP‐3 ratio levels. Serum cortisol concentrations were slightly but significantly increased by CR at 1 year only ( P  = 0.003). Calorie restriction had no effect on serum concentrations of PDGF‐AB and TGFβ‐1. We conclude, on the basis of the present and previous findings, that, in contrast to rodents, humans do not respond to CR with a decrease in serum IGF‐1 concentration or with a sustained and biological relevant increase in serum cortisol. However, long‐term CR in humans significantly and persistently increases serum IGFBP‐1 concentration.